The St. Thomas Christians Encyclopedia of India - A M Mundadan (Journal of Dharma, 1976)
The volume under review, the second of the 2 volume Encyclo- paedia of Christianity in India, is practically on Christians and Chris- tianity in Kerala. Volume II which is expected shortly will deal with Christians and Christianity in the rest of India.